An Analysis of the Relationship between Risk and Expected Return in Malaysia Stock Market: Test of the CAPM - Xin Rui, Koh; Rasiah, Devinaga; Yee Yen, Yuen; Ramasamy, Suganthi; Devi Pillay, Shalini (International Journal of Engineering and Technology, 2018)
Investment theory describes the concept of relationship between risk and return. Capital Model Asset Pricing Model (CAPM) was based on the risk and return relationship. CAPM described that assetâ€™s expected return that is above the risk free rate is directly related to the non-diversifiable risk that is measure by beta. Focus of this study is to identify the impacts of risk toward the stock return in Malaysia stock market during the year 2007 to 2015 by testing on the applicability of Capital Asset Pricing Model. The data is from monthly stock returns from 24 companies listed on the stock exchange for investigation. The analysis of monthly stock market closing indexes from using regression model was carried out on the standard CAPM model. When testing the CAPM model for the whole period, it has not showed strong evidence that support the validity of this model and in order to get better estimates, this study divided the whole sample into 3 sub periods of five years each. The study found high beta value does not related to higher level in stock return. The positive relationship between systematic risk and return does not have a strong evidence to support it. The research also identify that the securities market line has direct relationship between risk and return. The unsystematic risk does not have an effect on the return. It means that stock prices cannot be effectively predicted by CAPM and Malaysia Stock and the validity of CAPM does not exist in Malaysia Stock Exchange Market for the period 2007-2015 due to some limitations such as time frame, sample size and others. This paper suggest a different assets pricing model and takes into consideration of some related variables in predicting future stocks returns. This research provides important implication to investors, analysts, stock brokers, speculators, fund managers, practitioners, relevant authorities, and government.Â Â